A posteriori assessment of ecotoxicological risks linked to building a hospital. (February 2016) - Perrodin, Yves; Bazin, Christine; Orias, Frédéric; Wigh, Adriana; Bastide, Thérèse; Berlioz-Barbier, Alexandra; Vulliet, Emmanuelle; Wiest, Laure
Abstract: Hospital wastewater (HWW) contain a large number of chemical pollutants such as disinfectants, surfactants, and pharmaceutical residues. A part of these pollutants is not eliminated by traditional urban wastewater treatment plants (WWTP), leading to a risk for the aquatic ecosystems receiving these effluents. In order to assess this risk, we formulated a specific methodology based on the ecotoxicological characterisation of the hospital wastewater using a battery of three chronic bioassays ( Pseudokirchneriella subcapitata, Heterocypris incongruens and Brachionus calyciflorus ). We used it for the posteriori risk assessment of a hospital recently built in south-east France, and we studied the evolution of this risk during two years. We also used it to assess the decrease of the ecotoxicological risk after treatment of the effluent in a specific line of the local WWTP. Lastly, we compared these results with the risk assessment made before the building of the hospital in the context of a priori risk assessment. The results obtained showed an important evolution of the risk overtime, according to the hospital activities and the river flows, and a real decrease of the risk after treatment in the dedicated line. They also showed that the a priori assessment of ecotoxicological risks, made previously, was overstated, mainly because of the application of the precautionary principle. Highlights: Hospital effluents are generally discharged in sewers without treatment. A specific methodology has been developed to assess their ecotoxicological risk. It was applied on an experimental site before and after the building of the hospital. A comparison between the a priori and the a posteriori risks was then possible. In addition, a comparison of risks before and after treatment was carried out.